BCG VACCINE - AN INNOVATION FOR DIABETES TREATMENT IN PAKISTAN? - Lilani, Zohair; Ahmed, Afrinah; Tazeem, Rabbia; Naeem, Erum (Journal of Ayub Medical College Abbottabad, 2017)
Pakistan is a third world country with very small health budget and a diabetes prevalence of about 6.9% among adults, accounting for over 86,000 deaths. If phase 2 trials testing the ability of BCG to reverse type 1 Diabetes become successful in remission of insulin from pancreas this would be very useful to treat diabetes in Pakistan as BCG is readily available, less expensive, has less storage problems, less side effects and doesn’t require skilful person to administer. Keywords: Diabetes; BCG; Pakistan